2020
DOI: 10.1007/s00405-020-06301-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for irradiation vasculopathy by intima-media thickness sonography in head and neck cancer patients

Abstract: Purpose Post-irradiation vasculopathy is a severe form of atherosclerosis and affects the prognosis of head and neck cancer survivors. Sonographic intima-media thickness (IMT) precedes stenosis, plaque formation, and cerebrovascular events. Therefore, IMT may be a valuable screening marker for post-irradiation toxicity. However, the critical irradiation dose and the onset of IMT increase remain unclear. Methods The cross-sectional study analysed the carotid artery IMT in 96 irradiated patients and 41 controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Longitudinal studies showed higher IMTs in irradiated than in non-irradiated HNC survivors or healthy controls [ 3 , 5 ]. Also, as currently found, higher IMTs in irradiated than non-irradiated carotids in unilateral irradiated patients have been described [ 5 , 14 , 15 ]. Because the latter setting eliminates confounding effects of CVRFs, these results point to a specific cause-effect relation between radiation and carotid wall thickening.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Longitudinal studies showed higher IMTs in irradiated than in non-irradiated HNC survivors or healthy controls [ 3 , 5 ]. Also, as currently found, higher IMTs in irradiated than non-irradiated carotids in unilateral irradiated patients have been described [ 5 , 14 , 15 ]. Because the latter setting eliminates confounding effects of CVRFs, these results point to a specific cause-effect relation between radiation and carotid wall thickening.…”
Section: Discussionmentioning
confidence: 70%
“…So far, radiation dose has been associated with IMT [ 14 ], but not with carotid stiffness [ 12 ]. Relatively low radiation doses applied in this study could result in the lack of a dose–effect relation with IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Of those treated with radiation, 41 patients received bilateral neck radiation (M = 62.5 Gy ± 7.9), while 55 patients received tumor side boost (M = 61.1 Gy ± 9.7) with contralateral side receiving a lower dose (M = 49.3 Gy ± 15.6). Strüder and colleagues (2020) reported ultrasound measured a 13% mean carotid IMT increase in HNC patients after neck radiation vs. receiving neck dissection alone, and a 20% increase over healthy controls (radiation: n = 96, 0.77 mm ± 0.18; surgery: n = 21, 0.69 mm ± 0.10; control: n = 20, 0.64 mm ± 0.12; p < 0.05). This increase in carotid IMT was maintained over 10 years of follow-up.…”
Section: Resultsmentioning
confidence: 91%
“…A total of eight articles were reviewed, including four prospective studies ( Faruolo et al, 2013 ; Pereira Lima et al, 2011 ; Toprak et al, 2012 ; Wilbers et al, 2014 ) and four retrospective studies ( Gujral et al, 2016 ; Strüder et al, 2020 ; Yeh et al, 2019 ; Yuan et al, 2017 ; Table 1 ). Although these studies varied in design and included differing secondary endpoints, all reported post-radiation carotid IMT values and compared them to an external control population, an internal contralateral control, or internal control with measurements over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation